Upacara Kematian dalam Tradisi suku Toraja dalam Novel Puya ke Puya Karya Faisal Oddang: Kajian Sosiologi Sastra - Laili Ihsan, Nur (Humanis, 2018)
The object of this study is novel Puya ke Puya by Faisal Oddang.  Novel Puya ke Puya is analyzed using the theory of structure and the theory of sociology of literature. The using of sociologyof literature theory in this study is appropriate because the novel Puya ke Puya has a strong social view on the characters. The problems discussed are structural and social aspects of the Toraja contained in the novel Puya ke Puya. The structure of novel Puya ke Puya, include: characterization, plot and setting. Characterizations are divided into the main character and an additional character, the main character is Allu Ralla, additional characters are Rante Ralla, Tina Ralla, Malena, Maria Ralla, Mr. Berth, Mr. Soso and the Village Head. The plot of novel Puya ke Puya is chronological. Then the setting of place in novel Puya ke Puya is located in South Sulawesi Island, setting of time is in 2010, and the social background tell the life of the Toraja people. The social aspect of the Toraja in the novel Puya ke Puya, covering the economic, religious and cultural aspects. The economic aspect uncover the Toraja prosperity problems in society. The religious aspect explains the trust that connect people with the order of life. The cultural aspect explains the matters of custom and community habits.